ENHANCING STUDENTS’ SPEAKING SKILL IN FACING THE REVOLUTION ERA 4.0 - Rida Paranduk; Paula Rombepajung; Yofri Karisi (Journal of English Culture, Language, Literature and Education, 2021)
Many people think learning a language is easy because they assume we are using the language every day. Learning a language is not just being able to communicate with the language, but also know and understand the meaning contained in the word or phrase that pronounced. In study languages, especially English, most of the students experiencing difficulty in speaking or talking. Difficulty talk is usually caused by the difficult to express ideas orally, limited vocabulary, limited knowledge of grammar so it is difficult to talk with the correct rules, limited ability to properly pronounce vocabulary (pronounciation), so it is difficult to pronounce a word with true, the lack of courage to speak out because of fear of being wrong. To facilitate the ability to speak(speaking), there are some pretty effective way to try, among them: expand the vocabulary, read aloud,get to know the simple English,read English, conversation English, listening to English songs, watching English movies,love the subjects English. In this paper also discussed methods teaching role-play and media pictorial story to improve the ability of English-speaking students.